ANALISIS PENGARUH PENAMBAHAN ZAT ADDITIVE ISS 2500 TERHADAP KUAT TEKAN BATU BATA DENGAN DAN TANPA PROSES PEMBAKARAN - Febriantama, Aria; Afriani, Lusmeilia; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Brick is a material t h a t made of clay. Bricks were made with or without additional mixturel throughsome processes and stages. I n t his study used the clay with additional mixture 2500 ISS ( Ionic SoilStabilizer ) which has variety levels mixture of 0,9 ml, 1,2 ml , 1,5 ml and 2,1 ml with the intention to improvethe quality of brick. It is necessary to do the research , so this study can be compared with SNI standards.The tested samples in this study are clay that comes from jl . Nunyai , Rajabasa . It sample was curing for 7day and then, the samples will be done with or without burning process.Based on the results of physical testing the samples, USCS classify soil samples as clay with low plasticityand belongs to the ML group . After doing research of compressive strength testing of with and withoutburning process from four levels generating the compressive strength maximum average at a level of 2.1 mlboth of them. With value 21,24 kg / cm 2 for burning process and 4.25 kg / cm 2 for without burning process.Which is both of those treatments are not included into 25 classes based on tables strength of compressedbricks ( SNI 1991 ).Keywords: brick, clay, iss 2500 (ionic soil stabilizer), compressive strength.